Purchase Solution

# Change of Basis: Eigenvectors

Not what you're looking for?

For the problem, refer to the linear transformation T: R^3 --> R^3 given by T(x) = T(x, y, z) = (2x + 2z, x - y + z, 2x + 2z).
Write the change of basis matrix K from the basis F of R^3 which consists of the eigenvectors of T to the standard basis E for R^3.

##### Solution Summary

A change of basis matrix is found using eigenvectors. All work is shown in the solution.

##### Solution Preview

T(x, y, z) = (2x + 2z, x - y + z, 2x + 2z)

T(1, 0, 0)= (2, 1, 2)
T(0, 1, 0)= (0, -1, 0)
T(0, 0, 1)= (2, 1, 2)

Then the matrix is:

[2 0 2]

A= [1 -1 1]

[2 0 2]

We must find the eigenvalues of A and then find the eigenvectors of it:
The eigenvalues are 4, -1, 0. Then we have:

lambda=4 --->

...

##### Free BrainMass Quizzes

This quiz test you on how well you are familiar with solving quadratic inequalities.

##### Multiplying Complex Numbers

This is a short quiz to check your understanding of multiplication of complex numbers in rectangular form.